Treatment outcomes for patients with metastatic castrate‐resistant prostate cancer following docetaxel for hormone‐sensitive disease. Issue 1 (24th September 2020) - Schmidt, Andrew; Anton, Angelyn; Shapiro, Julia; Wong, Shirley; Azad, Arun; Kwan, Edmond; Spain, Lavinia; Muthusamy, Arun; Torres, Javier; Parente, Phillip; Parnis, Francis; Goh, Jeffrey; et al.
Abstract: Aim: Optimal treatment for newly diagnosed metastatic hormone‐sensitive prostate cancer (mHSPC) has evolved, with many patients deriving benefit from the addition of docetaxel to androgen deprivation therapy (D‐ADT). This study sought to define the therapy used and associated activity following D‐ADT. Methods: Retrospective analysis of patients with mHSPC treated with one or more cycles of D‐ADT who were identified from a prospectively maintained multisite prostate cancer database of patients treated in a community or academic center setting in Australia. The primary endpoint of this study was first‐line time to treatment failure (1L TTF) for subsequent treatment of metastatic Castrate Resistant Prostate Cancer (mCRPC), with secondary endpoints of prostate‐specific antigen (PSA) reduction >50% and time from 1L to second‐line (2L) treatment initiation. Results: A total of 93 patients received D‐ADT for mHSPC, 85 (91%) had subsequent treatment for mCRPC. Median time to mCRPC (biochemical, clinical or radiographic) had been 14.8 months (95% confidence interval [CI], 11.9–16.5). 1L treatment was enzalutamide 47 patients (55%), abiraterone 23 (27%), cabazitaxel 7 (8%), docetaxel 4 (5%) and other therapies 4 (5%). Median 1L TTF was 6.3 months (95% CI, 4.9–7.6), PSA > 50% reduction was achieved in 32 of 89 patients (36%), median time from 1L to second‐line treatment was 7.3 months (1.3–27.4), which did not differ significantly between treatment groups. Conclusions: Abiraterone, enzalutamide, cabazitaxel and docetaxel all demonstrate activity following progression on D‐ADT. No difference in efficacy was detected between treatment options for mCRPC. Prospective trials investigating the optimal treatment sequence for prostate cancer following progression on D‐ADT needed. Abstract : Docetaxel chemotherapy in combination with androgen depravation therapy (D‐ADT) is an established treatment for patients with newly diagnosed metastatic prostate cancer. The purpose of this study was to define the activity of treatments given following the failure of D‐ADT. No significant differences were identified between treatment options. Prospective trials are needed to identify the optimal therapy for patients in this setting.